On the Role of Mass Media in Promoting The Mission of Russian Education Policy (A Case Study of Talk Shows) - Nadezhda Radina; Svetlana Shamanina (Voprosy obrazovaniya / Educational Studies Moscow, 2015)
The paper presents results of analyzing the 2012–2013 episodes of talk shows broadcasted by regional (Challenges of Life, NNTV channel, Nizhny Novgorod) and national (Let Them Talk, Channel One OJSC) channels devoted to education and education policy issues. The need for research reflection on these materials was justified by studying the documents of the recent years regulating the Russian education policy (laws, bylaws, programs, conventions, etc.), which allowed us to identify the key priorities of this policy: solving the staffing problem, enhancing the quality of education, improving its transparency, and equalizing education in Russia. Narrative analysis was performed to study the talk show data, namely we used open coding with creation of a coding system based on utterance qualitative assessment and with subsequent use of statistical procedures to analyze the data matrix. We also used the social problem rhetorical deconstruction method offered by Ibarra and Kitsuse. Based on the data obtained, we describe two education policy promotion strategies: 1) instruction and enlightenment integration of education policy principles and practices), realized to some extent in the regional talk show, and 2) entertainment and control (accentuated negative practices of controlling viewers’ minds through emotional pressure and shock) used in the One Channel talk show. We also discuss the attitude of the State towards such mass media strategies and the quality of media ef fects caused by talk shows in terms of education policies.